3(6x+1)=-10+5(2x+1)

Simple and best practice solution for 3(6x+1)=-10+5(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(6x+1)=-10+5(2x+1) equation:


Simplifying
3(6x + 1) = -10 + 5(2x + 1)

Reorder the terms:
3(1 + 6x) = -10 + 5(2x + 1)
(1 * 3 + 6x * 3) = -10 + 5(2x + 1)
(3 + 18x) = -10 + 5(2x + 1)

Reorder the terms:
3 + 18x = -10 + 5(1 + 2x)
3 + 18x = -10 + (1 * 5 + 2x * 5)
3 + 18x = -10 + (5 + 10x)

Combine like terms: -10 + 5 = -5
3 + 18x = -5 + 10x

Solving
3 + 18x = -5 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
3 + 18x + -10x = -5 + 10x + -10x

Combine like terms: 18x + -10x = 8x
3 + 8x = -5 + 10x + -10x

Combine like terms: 10x + -10x = 0
3 + 8x = -5 + 0
3 + 8x = -5

Add '-3' to each side of the equation.
3 + -3 + 8x = -5 + -3

Combine like terms: 3 + -3 = 0
0 + 8x = -5 + -3
8x = -5 + -3

Combine like terms: -5 + -3 = -8
8x = -8

Divide each side by '8'.
x = -1

Simplifying
x = -1

See similar equations:

| .0000852x^2-.0122x+.0514=0 | | 3(2x-5)=3-4(x+2) | | 3m+5=3-5m | | -x^2+14x-13= | | -7x-12=-9 | | 2x+5+3x=25 | | 28x^2-3x-1=0 | | 49x^2+70x+25= | | 2t^5-14t^4+20t^3= | | 2t^5-14t^4+20t^4= | | x^2+10x-224=0 | | (x-4)(x+9)=0 | | (2u+18)(u^2-9)=0 | | 2.5x+0.25x=1.25+x | | x^5-11x^4-26x^3= | | 4x-7=8+2x | | 4x^2+32x-80= | | 24-y=5y | | 4(a+3)=11 | | 0.21y-0.8=0.11y+1-0.8y | | t(t+5)=2t^2+7 | | (x+7)(x+7)=2x^2+13x+19 | | 5m-26=-25+6m | | 5x^2-40x^2+75x= | | 3(5x+1)+6(5x+1)=2 | | .8m-.2m=9 | | 2x^4-3x^3+2x^2-15x+14=0 | | u^2-6u+8=0 | | -32xy^5+40x^3y^5-16xy^5= | | 8y=7y-45 | | 3t^3-9t+6=0 | | 27c^4-125c=0 |

Equations solver categories